Excitonic interaction amongst InP/ZnS salt pellets. Issue 29 (17th July 2017) - Altintas, Yemliha; Faruk Yazici, Ahmet; Unlu, Miray; Dadi, Seyma; Genc, Sinan; Mutlugun, Evren
Abstract : FRET enabled Cd-free quantum dot pellets for white light generation has been demonstrated. Abstract : Salt matrix has recently been introduced as a promising robust platform for embedding colloidal quantum dots to provide them with photo stability for versatile applications. This work demonstrates the excitonic interaction amongst high efficiency colloidal InP/ZnS quantum dots embedded in a KCl salt matrix. By varying the donor acceptor ratio within the solid platform, 65% Förster Resonance Energy Transfer (FRET) efficiency was attained. Optimizing the donor : acceptor ratio, we demonstrated the first FRET-enabled Cd-free pellets for white light generation possessing a color rendering index (CRI) of 84.7, correlated color temperature (CCT) of 5347.5 K, and a high luminous efficacy of optical radiation value (LER) of 324.3 lm/ W opt . Our study of excitonic interactions within quantum dot-loaded salt matrices will open new possibilities for future versatile optoelectronic applications.